Estudo comparativo da resistência à corrosão entre o aço Inoxidável duplex AISI 2205 e o aço inoxidável austenítico AISI 304 quando imersos em uma solução aquosa contendo 0,6m de cloreto de sódio - Sousa, Ruth Anne Paxele de (Universidade Federal Rural do Semi-Árido, 2018)
The duplex stainless steel AISI 2205 belongs to a class of materials with biphasic microstructure, consisting of a ferritic matrix and austenite islands, with approximately equal volume fractions of that phase. This class stands out by the excellent combination of its mechanical properties and resistance to corrosion. The AISI 304 austenitic stainless steel has an initial monophasic microstructure composed of almost equiaxial austenite grains, which are used in the Brazilian industry as well as the duplex stainless steel. Due to the fact that these two steels present good corrosion resistance together with their employability in the industrial sector, this work will be carried out with the purpose of promoting a comparative study between AISI 2205 duplex stainless steel and AISI 304 austenitic stainless steel evaluating the resistance to corrosion. corrosion when subjected to a corrosive medium - sodium chloride, as well as the effect of temperature and time of heat treatment on the corrosion resistance of steel. For this the behavior of these steels after heat treatment at a temperature of approximately 1060 ° C for a time of 1 hour was analyzed by optical microscopy and potentiodynamic polarization assay. Optical microscopy was used to observe changes in microstructure after heat treatment and polarization curves to evaluate corrosion resistance. Under the imposed treatment conditions, the increase in temperature with the heat treatment reduces the corrosion resistance of duplex stainless steel and austenitic stainless steel.
Monografia
Keywords: Aço inoxidável duplex; Resistência à corrosão; Aço inoxidável austenítico; Stainless steel duplex; Corrosion resistance; Austenitic stainless steel; ENGENHARIAS::ENGENHARIA MECANICA